Toll-like receptor signaling pathway involved in pathogenesis of thromboangiitis obliterans through activating of NF-κB - Guo, Facai (2024)
Objectives: The pathogenic mechanisms of Thromboangiitis Obliterans (TAO) are not entirely known and autoimmune inflammation plays a vital role in the initiation and continuance of TAO activity. The authors investigated in this study the role of the TLR signaling pathway in the pathogenesis of TAO. Methods: First, the authors detected the expressions of MyD88, TRIF and NF-κB in vascular walls of 46 patients with TAO and 32 patients with trauma and osteosarcoma by western blot assay. Second, the authors detected the cellular localization of MyD88, TRIF and NF-κB in vascular walls of patients with TAO by immunofluorescent assay. Results: The protein expressions of MyD88, TRIF and NF-κB were much higher in vascular walls of TAO patients (p < 0.05). Higher expressions of MyD88 and NF-κB were detected both on vascular endothelial and vascular smooth muscle cells of TAO patients. However, higher expression of TRIF was just detected on vascular smooth muscle cells of TAO patients. Conclusions: These dates suggest that the TLR signaling pathway might play an important role in the pathogenesis of TAO, it might induce vasospasm, vasculitis and thrombogenesis to lead to the pathogenesis and progression of TAO.